The Effect of Glyphosate Harbicide on Soil Fungi - Bashir, M.; Isa, H.; Adamu, M. K. (UMYU Journal of Microbiology Research)
Glyphosate herbicide is one of the herbicide used throughout the world and they are very important to agriculture. Despite the role of glyphosate herbicide to agriculture, they also posed direct or indirect threats to the health of humans and also to the nature and survival of soil microorganisms. This study was carried out to determine the effect of glyphosate herbicide on soil fungi. Enumeration of fungal population in the soil samples before and after treatment was carried out. The fungal count was found to be 2.8x103cfu/g before the treatment with glyphosate herbicide and the number continue to decrease up to 0.4x103cfu/g in the 15day of glyphosate herbicide treatment. The fungal population decreased upon treatment with glyphosate herbicide when compared to the control i.e. the untreated soil sample. Glyphosate herbicide causes greater reduction in fungal count because the fungal populations decreased gradually and complete disappearance of some species after 6 days of treatment and continue to decrease up to 15 days after treatment. Soil fungi were isolated from the soil before the application of glyphosate herbicide; they include A. niger, A. flavus, Penicillium spp., Microsporium spp. Trychophyton spp. upon application of glyphosate herbicide, not all the fungi isolated before treatment survive the effect of glyphosate herbicide. The most frequently isolated fungi that survive up to 15 days of treatment is Aspergillus species (A. flavus and A. niger) while Microsporium spp., Trychophyton spp. and Penicillium spp. disappeared completely after 9 days of treatment.